Physical activity intensity and subjective well-being in healthy adults. (August 2019) - Panza, Gregory A; Taylor, Beth A; Thompson, Paul D; White, C Michael; Pescatello, Linda S
The effect of physical activity intensity on subjective well-being has not been well established. We examined this relationship among 419 healthy adults using objective and subjective physical activity measurements (sample size varied among well-being assessments). For accelerometers, light-intensity physical activity positively associated with psychological well-being ( n  = 150) and negatively associated with depression ( n  = 99); moderate intensity negatively associated with pain severity ( n  = 419) and positively associated with psychological well-being; sedentary behavior negatively associated with psychological well-being and positively associated with depression ( p s < .05). These findings were generally consistent with subjective measurements of physical activity (Question 8, Paffenbarger Questionnaire). Higher levels of sedentary behavior are associated with lower subjective well-being.